Coronary Artery Spasm; Frequency and Angiographic Findings in the Iraqi center for heart diseases (Single Centre experience) - Al-Najjar, Hassan Y.; Omran, Ammar Z.; Al- Najjar, Zaid A. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Coronary artery spasm occurs spontaneously leading to the syndrome of variant angina. It occurs in about 15 % of patients undergoing coronary angiography.Objectives: This study sought to estimate the rate of coronary artery spasm that occurs during coronary angiography and percutaneous coronary intervention with their risk factors in patients admitted to the Iraqi center for heart disease.Methods: This is a cross sectional observational study, We prospectively collected the data of patients over six months period (from August 2014 till February 2015 ) who developed coronary artery spasm during cardiac catheterization (diagnostic and therapeutic).Results: Out of 1274 patients, 106 patients developed coronary artery spasm(8.3%). 71.6% of patients were adult aged 50-69 years.74.5% patients were males (P.V 0.0001).Smoking was a strong risk factor for the coronary artery spasm (P.V